Extrapulmonary Paragonimiasis Diagnosed by Molecular Tools - Da Young Kim; Jun-Won Seo; Na-Ra Yun; Dahae Kwak; Choon-Mee Kim; Dong-Min Kim (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Paragonimiasis is a parasitic disease that involves the lungs but can manifest in extrapulmonary sites, including the peritoneum or subcutaneous tissue. Diagnosis is limited by nonspecific clinical manifestations and overlapping features with other diseases, such as tuberculosis (TB). A 55-year-old Korean male presented with acute abdominal pain and a recurrent subcutaneous mass in the left thigh. Although TB peritonitis was initially suspected, further diagnostic tests were performed. To confirm the diagnosis, multiplex real-time polymerase chain reaction (PCR) targeting the 28S rRNA gene and conventional PCR targeting the ITS2 region were performed on the ascitic fluid. Sequence analysis and phylogenetic clustering confirmed Paragonimus westermani . The patient was treated with praziquantel and showed clinical improvement. This case highlights the importance of considering paragonimiasis in patients with unexplained eosinophilia and peritoneal symptoms, even in the absence of pulmonary involvement. Molecular diagnostic tools can help confirm extrapulmonary infections and prevent misdiagnosis, particularly in endemic regions.